2018
DOI: 10.1002/sia.6543
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative XAFS/EELS analyses of nitrogen species in titanium oxide photocatalysts

Abstract: With a view to rational designing of a highly functional visible‐light TiO2 photocatalyst, nitrogen atoms were doped into TiO2 samples by an ion implantation technique which enables to control the depth and concentration of dopants. Although the absorbance in the visible‐light region of the sample increased by the nitrogen doping, photocatalytic activity of the sample was not directly connected with the photo‐absorbance. The N K‐edge X‐ray absorption near edge structure (XANES) spectrum of the photocatalytic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Yoshida et al have researched on the photo‐catalytic decomposition of methylene blue by visible light in N implanted TiO 2 . [ 264 ] The results indicate that nitrogen implanted into TiO 2 results in attachments as Ti ((N)s) and NO 2 ((NO 2 )s), and the former is believed to dominate in the active sample, and the latter in the inactive sample. Wu et al have substantially extended the range of light harvesting of TiO 2 NW by nitrogen implantation.…”
Section: Optical Applications Of Ion‐implantation In Tio2mentioning
confidence: 99%
“…Yoshida et al have researched on the photo‐catalytic decomposition of methylene blue by visible light in N implanted TiO 2 . [ 264 ] The results indicate that nitrogen implanted into TiO 2 results in attachments as Ti ((N)s) and NO 2 ((NO 2 )s), and the former is believed to dominate in the active sample, and the latter in the inactive sample. Wu et al have substantially extended the range of light harvesting of TiO 2 NW by nitrogen implantation.…”
Section: Optical Applications Of Ion‐implantation In Tio2mentioning
confidence: 99%
“…There are however, studies in the literature using N K-edge energy loss near edge structures spectra to investigate N containing transition metals. This technique can enable further interpretation of features seen in the X-ray absorption near edge structure (XANES) spectra and allow for investigation of the electronic structure and bonding of these species 2527. In addition, studies using N K-edge on solids has been shown to provide information on changes in the local structure surrounding N atoms in these materials.…”
Section: Introductionmentioning
confidence: 99%
“…The characteristic double-peaked structure appeared at around 396–402 eV in TiO x N y decreased with the oxidation temperature. Instead, a sharp single peak at 400 eV appeared which was attributed to the formation of O–N–O in TiO x N y . With higher temperature oxidation (see O X TON-673 K (2%) in Figure ), the double-peaked structure changed to the single peak.…”
Section: Discussionmentioning
confidence: 97%
“…Instead, a sharp single peak at 400 eV appeared which was attributed to the formation of O−N−O in TiO x N y . 19 With higher temperature oxidation (see O X TON-673 K (2%) in Figure 4), the double-peaked structure changed to the single peak. As N K-edge XANES in the total electron yield mode gives information on depth within 10 nm from the surface, the oxidation changed the boding of O−Ti−N near the surface of TiO x N y to O−N−O.…”
Section: Acs Omegamentioning
confidence: 99%